Guidelines for Managing Learning Resources in Schools in the Digital Era under the Secondary Educational Service Area office Nonthaburi - Pauvong, Somkuan; Phongcharoen, Chomkhae (Journal of Graduate MCU KhonKaen Campus, 2026)
The objectives of this research were to 1) study the management of school learning resources in the digital era; 2) to compare on the management of school learning resources in the digital era classified by gender, age, educational, work experience, and school size; and 3) study the guidelines for management of school learning resources in the digital era. The samples consisted of 320 teachers and 5 school administrators under the Secondary Educational Service Area Office, Nonthaburi Province selected through stratified random based on school size. The research instrument was a interview and questionnaire with content validity, IOC values between .67 to 1.00 and a reliability coefficient of .98. The data were analyzed by using frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, LSD and content analysis. The research results were as follows 1) the management of school learning resources in the digital era was high level with descending particular aspects of implementation, planning, conclusion and development, and evaluation; 2) compare on the management of school learning resources in the digital era classified by gender, age and educational were not difference, while the differential work experience, and school size were statistically significant at the level of .05 3) the guidelines for management of school learning resources in the digital era should involve administrative support in terms of resources, technology, and fostering positive attitudes to enhance motivation among teachers and students for effective and sustainable use of digital learning resources.